ANALYSIS OF STUDENTS' ERRORS IN ANSWERING MATHEMATICAL LITERACY QUESTIONS - Sitti Nurazizah; Miftahul Azira; Muhammad Zulhajji Rezky; Adnin Asyifa; Nurul Ainun Fajriah (Hipotenusa Journal of Research Mathematics Education (HJRME), 2025)
Mathematical literacy-based problems require the ability to read, interpret and connect contextual information with mathematical concepts, which is often a challenge for students. This difficulty is especially evident in modulo congruence material which requires an understanding of number concepts and mathematical logic. This study aims to analyze students' errors in solving mathematical literacy problems related to modulo congruence material. The research subjects were ten grade XI students from one of the high schools in Gowa Regency who were selected by purposive sampling. The method used was a written test to identify the types of errors, as well as in-depth interviews to explore the causes. The results showed that students had difficulty in understanding important information from the problem, translating it into a mathematical model, and composing the solution steps systematically. The conclusion of this study shows that learning interventions are needed that focus on strengthening context understanding, practicing reading problems critically, and habituation to develop coherent solution strategies. In addition, gradual integration of mathematical literacy exercises needs to be done so that students are able to develop mathematical thinking skills as a whole. Keyword: Error Analysis, Math Literacy Problem, Congruence, Modulo